Analisis Nilai Kalor dan Laju Pembakaran Arang Cangkang Buah Karet - Hadijah, Siti; Mutiarani, Azizah; Masturi; Yulianti, Ian (Universitas Nurul Huda, 2022)
Rubber fruit shells are found as agricultural waste. Many farmers have not used rubber fruit shells. Therefore, the researchers made alternative fuels from rubber fruit shells containing 60-80% cellulose and 5-20% lignin. The research objective was to analyze the calorific value and burning rate of rubber fruit shell charcoal. The combustion rate test is carried out by burning charcoal and measuring how long it takes to turn into ash, and the mass of the burned ash. The heating value is done by making a simple furnace from a can filled with charcoal with a mass of 5g, 10g, 15g, 20g, 25g and 30g. 200ml of water is placed on the stove until it boils, measure the time and temperature when it boils. The result of the longest burning rate is 2.12g / minute. The heating value that results in high temperatures and large coals is 332.4 kJ. The conclusion of this study is that rubber fruit shells which have a large mass are very good to be used as an alternative fuel with a very high combustion rate and calorific value.